Amino acid digestibility and energy concentration of fermented soybean meal and camelina meal for swine - Graham, A. B.; DeRouchey, Joel M.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S.; Thaler, R. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Two experiments were conducted to determine the amino acid and GE digestibility of fermented soybean meal and camelina meal. For Exp. 1, to determine standardized ileal amino acid digestibility, five growing gilts (BW= 60.4 lb) were surgically fitted with T-cannulas at the terminal ileum and randomly allotted to 1 of 3 dietary treatments in a crossover design with 3 periods. The basal diets were corn starch–based with adequate vitamins and minerals to meet the pigs’ requirements. The experimental treatments consisted of the basal diet with 30% fermented soybean meal or 39.25% camelina meal as the sole protein sources. A third nitrogen-free diet was also fed to determine basal endogenous amino acid losses. For Exp. 2, to determine energy concentrations, 6 growing barrows (BW = 64.8 lb) were randomly allotted to 1 of 3 dietary treatments in a crossover design with 3 periods. The corn-based treatment diets had 25% fermented soybean meal or 30% camelina meal. A third corn basal diet was also offered to allow for energy calculations by the difference method. All diets contained 0.25% titanium oxide as an indigestible marker. Digesta samples were collected and analyzed for amino acid concentrations, and fecal samples were collected and analyzed for energy concentrations. After chemical analysis, standardized and apparent ileal digestible (SID and AID, respectively) amino acids were determined, and DE, ME, and NE were calculated for each ingredient. On a DM basis, GE, DE, ME, and NE were 1,973, 1,377, 1,232, and 880 kcal/lb, respectively, for fermented soybean meal and 2,075, 1,150, 1,041, and 715 kcal/lb, respectively, for camelina meal. In fermented soybean meal, the AID for lysine, methionine, threonine, and tryptophan were 63.5 ± 7.5, 84.6 ± 1.0, 74.0 ± 3.5, and 81.8 ± 1.4%, respectively, and SID values were 71.1 ± 6.2, 89.2 ± 2.1, 88.0 ± 3.1, and 93.7 ± 2.0%, respectively. For camelina meal, the AID for lysine, methionine, threonine, and tryptophan were 47.3 ± 7.7, 74.6 ± 3.3, 39.7 ± 6.8, and 67.3 ± 8.3%, respectively, and SID values were 53.9 ± 6.4, 77.7 ± 3.5, 51.6 ± 6.7, and 79.7 ± 6.8%, respectively. The SID availability for amino acids in fermented soybean meal were relatively high and similar to published values for soybean meal, with the exception of lysine. Standardized ileal digestible amino acid availability values for camelina meal were low, indicating that it may have contained the high glucosinolate concentrations generally observed in camelina meal.
Keywords: Camelina meal; Fermented soybean meal; Digestibility; Finishing pig